Evaluation of five standard protocols for the obtention of canine platelet rich plasma - Fariña Sirandoni, Pablo Antonio; Pulgar Aguila, Rodrigo Ambrosio; Molina Cofré, Alejandro Ignacio (Spei Domus, 2020)
Introduction: platelet rich plasma (PRP) usage has acquired great relevance within the last few years, which has demonstrated its usefulness in the treatment of some pathologies. Up until now, there is not enough information on efficient obtention processes that warrants a wished minimal concentration for therapeutical purposes. This study compared five known protocols for PRP obtention and stablished the best performance to determine which protocol offers the greatest number of platelets with common resources within the clinic. Methodology: five standard protocols recommended by international literature were compared by its capacity to accomplish larger amounts of platelets. Canine blood with a normal hemogram was used to evaluate each protocol by counting each PRP number. Results: a platelet count was carried out and it was found that 163% for protocol C, followed by protocol B, E, D and A with 96%, 8.62%, 6.38% and 4.47%, respectively. Conclusions: there is a great variability between platelet count within each protocol. In this case, protocol C gave the best result, being the one that demands more revolutions and time for the obtention of PRP.